Hồ Chí Minh toàn tập. T.6, 1950-1952. (Hà Nội : Chính trị quốc gia, 2004)
Các tác phẩm, bài nói, bài viết quan trọng của Chủ tịch Hồ Chí Minh từ năm 1919 đến năm 1969.
Keywords: Hồ Chí Minh, -- 1890-1969.; Hồ Chí Minh; Hồ Chí Minh, -- 1890-1969.